Aminosalicylic Acid Hydrazone Dioxomolybdenum(VI) Complex: Synthesis, Spectral Characterization and Application as a Green Homogeneous Lewis Acid Catalyst for the One-Pot Three-Component Synthesis of 2-Amino-3-Cyano-4H-Pyrans. (21st October 2022) - Kargar, Hadi; Fallah-Mehrjardi, Mehdi; Munawar, Khurram Shahzad
Abstract: A dioxomolybdenum(VI) complex has been successfully prepared by the reaction of an ONO donor Schiff base, derived by condensing 3-methoxysalicylaldehyde and 4-amino-2-hydroxybenzohydrazide, with MoO2 (acac)2 . The structures of synthesized products were explored spectroscopically through FT-IR, 1 H and 13 C NMR and by elemental composition (CHN) through combustion analysis. The catalytic potential of the complex was explored to synthesize the substituted 4 H -pyrans through the domino Knoevenagel condensation, Michael addition and cycloaddition reaction. In this method, three-component condensation of various aryl aldehydes with malononitrile and 1, 3-dicarbonyl compounds was carried out in refluxed ethanol. The main advantages of the present catalytic work are less time required for the completion of the reaction, high percentage yield and simplicity in operation.